La política nacional/internacional de las telecomunicaciones en América Latina - Plaza, Oscar (Estudios Internacionales, 2001)
This paper examines the telecommunications policies applied in Latin America in the last two decades. According to the particular reading that is made of these policies, they would not be the linear result of the economic policies in practice. Consequently, the study proposes that the adoption and implementation of national telecommunication policies in Latin America are the result of a complex coupling between current economic policies and technological developments and international telecommunications policies. The meeting of these components would have created the political scenario in which telecommunications in the region have had to develop.